Research Paper: Ab-Initio Simulation of the I-V Curve of Polyphenylene-Based Molecular Diodes: The Role of Electrode - Mansoure Ilkhani; Reza Faghih Mirzaee; Shadi Sadeghian (فیزیک کاربردی ایران)
This research aimed to focus on polyphenylene (C6H4)n-based molecular electronic wires that have a current density ten times that of carbon nanotubes. The transport properties in polyphenylene molecular devices were simulated with two different metal electrodes using ab- initio code based on the density functional theory (DFT) as well as the non-equilibrium Green's function (NEGF).  First, the structure of polyphenylene (C6H4)n, nitrobenzene C6H5NO2, and aniline C6H5NH2 molecules was created and relaxed using SIESTA code. Then, the circuits were simulated and relaxed by two different types of electrodes of gold and silver using sulfur clamps. The passing flow through each circuit was calculated in the voltage range of -2V to +2V in spin and non-spin mode using TranSIESTA code to investigate the transfer properties. The results indicated that the use of gold electrode increased the current passing through the circuit. Examination of the upper and lower spins showed that there was no significant difference in the conduction of electrons with up and down spins.